Food and Local Social Harmony: Pork, Communal Dining, and Muslim-Christian Relations in Flores, Indonesia - Yohanes S. Lon; Fransiska Widyawati (Studia Islamika, 2019)
This study explores the relations between Catholics and Muslims in Manggarai based on their different perspectives on pork being served in communal dining settings. Pigs carry significant meaning for people in Manggarai as a sacrificial animal, a symbol of culture and belief, which is why pork has been served as the main course at various celebrations. It is common for a Muslim family to provide pig at certain rituals, notwithstanding the fact that they will not eat it. To cater to Muslim families, Catholic families have a tradition called woni, whereby they serve their Muslim guests a pork-free ‘special menu’. This tradition, however, has become less popular over the past few years because of its sensitive and conflicting nature. Through a socio-historic approach, this study argues that food can be a medium to both strengthen and sever inter-faith relations. This includes a closer look at a new dakwah movement, the politics of identity, religious conflicts, majority-minority tensions in Indonesia and abroad are also key factors that can affect Catholic-Muslim relations in Manggarai.